Analysis of Imaging Results for Semisitting Compared with Supine Positioning in the Retrosigmoid Approach for Resection of Cerebellopontine Angle Vestibular Schwannomas. Issue 3 (21st March 2023) - Arambula, Alexandra M.; Wichova, Helena; Lucas, Jacob C.; Schelbar, Natalie; Harn, Nicholas; Ledbetter, Luke; Chamoun, Roukoz B.; Camarata, Paul J.; Lin, James; Staecker, Hinrich
Abstract : Objective: To compare the completeness of resection of vestibular schwannomas using three-dimensional segmented volumetric analysis of pre- and postoperative magnetic resonance imaging (MRI) of patients undergoing supine and semisitting positioning for the retrosigmoid approach. Study Design: Retrospective chart review. Setting: Tertiary medical center. Patients: Patients with vestibular schwannomas undergoing surgical resection via the retrosigmoid approach. Intervention(s): Tumor resection via the retrosigmoid approach with different patient positioning: standard supine versus semisitting. Main Outcome Measure(s): Preoperative versus postoperative three-dimensional segmented volumetric MRI analysis of vestibular schwannomas. Results: A total of 43 patients (15 supine and 28 semisitting) underwent retrosigmoid craniotomy for resection of vestibular schwannomas. For the conventional supine and semisitting positioning, mean preoperative tumor volumes were 12.65 and 8.73 cm 3 ( p = 0.15), respectively. Postoperative mean tumor volumes for the supine and semisitting positions were 2.09 and 0.48 cm 3 ( p = 0.13), respectively. There were 11 cases of postoperative sigmoid sinus thrombosis, 3 in the conventional supine group and 8 in the semisitting groups, and there were 6 cases of postoperative cerebrospinal fluid leaks, all in the semisitting group. The mean House–Brackmann scores for the supine and semisitting groups were 2.9 and 2.3, respectively. There was no statistically significant difference between groups in the rates of these or any other postoperative complications. Conclusions: The semisitting position for the suboccipital retrosigmoid approach for vestibular schwannoma resection does not compromise the ability to adequately resect the tumor as seen by volumetric MRI results. Further studies are needed to establish the safety of this position compared with the traditional supine approach.